Percepção dos fumicultores expostos à agrotóxicos sobre a qualidade de vida: ênfase nas condições de saúde geral e auditiva - Cazé, Ana Maria de Barros (2015)
Brazil ranks first in the world in export of tobacco and second in production. AFUBRA (2013) However tobacco farming uses large quantities of pesticides. Paraná is the third largest consumer of pesticides in the country. (IPARDES, 2010) Since Brazil is the world's largest consumer. (ABRASCO, 2012) Because of the need for tobacco growing the use of pesticides is an activity that offers great danger to producers and family, Silva et al. (2005), The Ministry of Health describes the tobacco culture exposes workers to various risks because of the high application of pesticides needed to control pests, weeds and fungal diseases that prevent the growth of smoking. (BRAZIL, 2008) According to the International Labour Organization / World Health Organization (ILO / WHO), pesticides annually cause 70,000 acute and chronic poisoning progressing to death and at least 7 million acute and chronic non-fatal, bringing severe health consequences human and environmental degradation risk, caused by abusive and inappropriate use of these chemicals (Faria; Fassa; Facchini, 2007). The losses in general and auditory health, arising from exposure to pesticides can cause impact on people's quality of life. The purpose of this study was to analyze the perception of tobacco growers exposed to pesticides on the quality of life with emphasis on general and auditory health. It is a descriptive, of the transversal type with a quantitative approach, conducted in the municipality of Rio Azul-PR, with tobacco growers. Data were collected from November 2012 to November 2014, after explicit consent of the subjects. For data collection, we chose an instrument already validated, the SF-36 and two questionnaires prepared by the working core, health and UTP society with closed questions on working conditions, health and hearing health. We evaluated 78 subjects, 40 tobacco farmers (study group) and 38 residents of Blue River, (control group) did not occupationally exposed to pesticides. The results showed that tobacco growers had worse quality of life scores compared to the control group, significant differences were observed in the pain domain (p = 0.043) and general health (p = 0.009). There was a significant relationship between the domain physical aspects and chronic diseases (p= 0.0302 ) . And significant relationship between the domains : functional capacity and hearing complaints ( p=0.0077 ) , physical aspects and hearing complaints ( p= 0.0304 ) and general health and hearing complaints (p= 0.0100 ). It concludes that the tobacco farming because of the risks of work activity , especially the use of pesticides , have impairments in quality of life.